Investigation of the molecular and mechanistic basis for the regioselective metabolism of midazolam by cytochrome P450 3A4. Issue 14 (23rd March 2022) - Fu, Tingting; Zheng, Qingchuan; Zhang, Hongxing
Abstract : The molecular mechanism of the regioselective metabolism of midazolam by CYP3A4. Abstract : Cytochrome P450 3A4 (CYP3A4) is the most important P450 enzyme for drug metabolism and drug–drug interaction, due to it being responsible for the biotransformation of approximately 50% of clinically used drugs. Advance knowledge of the molecular and mechanistic basis of CYP3A4 regioselective metabolism is beneficial for understanding the production of metabolites, and may allow personalized metabolic pathways or designing pathway-specific therapeutics. In this work, we focus on investigating the ligand–receptor interactions, substrate conformational transition, and key factors regulating the specificity of metabolic pathways using midazolam (MDZ) as a probe. Here, three types of substrate-binding conformations related to the diversity of MDZ metabolites are identified. The results also suggest that an allosteric site for MDZ is located near the F′-helix, A-anchor, and C-terminal loop of CYP3A4. The presence of an effector in the allosteric site can accelerate the conformational transition of the substrate via modulating a "sandwich" structure, and may affect the proportion of metabolites at high substrate concentration. We hope that the results can improve the understanding of the CYP3A4 structure and function, and provide a new perspective for drug development.